The construction of pad footing / Muhammad Firdaus Razali - Razali, Muhammad Firdaus (Universiti Teknologi MARA, Perak, 2022)
Footing are one of the most important structure elements of a building. It is the core structure of a building and the head structure. Its constructed by digging hole to the ground, fit and finish with concrete and land filling .However, currently there is limited research conducted on proper construction of pad footing especially in residential building. Therefore, this report will discuss about work for the pad footing of the residential building. This report was conducted for The Construction of One Storey Bunglow House at No 14, Jalan Utaman, Felcra Nasaruddin 32600 Bota, Perak Darul Ridzuan that owned by Tuan Ali Osman.The objectives of this report is to describe the construction method of pad footing, to analyze time and cost for construction of foundation/footing and to determine the problem and solutions taken to solve the problem. In addition this study also using 3 appropriate method for example observation, interview, documentation analysis and internet research. As a result to construct the pad footing there are 9 steps to follow. These are planning, site clearance, crafting work, setting out, reinforcement bar and formwork installation, concreting work, stump and back filling.However, there are problem during the construct the pad footing for example the problem related with weather and workers. As the conclusion, the pad footing are important to the building because it is the core structure. Therefore knowing the proper construction of pad footing is required for contractor and workers to construct pad footing accordingly to achieve time,cost ,quality and safety.